Analisis Laporan Arus Kas Dalam Menilai Kinerja Keuangan PT. Sumber Satwa Sejahtera - Daulay, Amelia Putri; Syafina, Laylan (Balance : Jurnal Akuntansi dan Manajemen, 2022)
The purpose of this study was to determine the description of the cash flow statement and financial performance at PT. Sumber Satwa Sejahtera uses a cash flow ratio analysis that tends to increase. This research was conducted using descriptive analysis method with a quantitative approach. The type of data used in this study is cumulative data, namely the company's financial statements in the form of balance sheets, income statements and cash flow statements at PT. Prosperous Animal Resources for the 2019-2021 period. Data collection techniques used in this research are library research and documentation research. The results of this study concluded that financial performance as measured by the ratio of operating cash flows to current liabilities, the ratio of operating cash flows to capital expenditures, the ratio of operating cash flows to total debt and the ratio of operating cash flows to net income tends to increase